Commented review of the Colombian legislation regarding the ethics of health research - Mónica María Lopera (Biomédica: revista del Instituto Nacional de Salud, 2017)
The scope of ethics in health research transcends its legal framework and the regulations established in Resolution 8430 of 1993. These norms represent a fundamental tool to determine the minimum protection standards for research subjects, and, therefore, they should be known, applied properly, and reflect upon by all researchers in the field. Here I present and discuss from an analytical point of view the regulations that guide research in health. In this framework, health is understood as a multidimensional process, and research in health as a multidisciplinary exercise involving basic, clinical and public health research, collective health, and other related sciences. The main analytical categories are related to the principles and actors involved in research (regulatory authorities, ethical committees, and special or vulnerable subjects and populations), and to professional ethics codes, in addition to informed consents and data management. Despite the contribution of this legislation to the qualification of health research, my conclusion is that the national legislation in ethics for health research requires updating regarding technological and scientific developments, as well as specifications from the multiple types of health studies.